Enhancing Canadian‐German partnerships in the mining industry. Issue 1 (April 2014) - Schmidt, Christopher; Ermolaeva, Alexandra
Abstract The German industry is highly dependent on imports of metals and industrial minerals. The Canadian mineral resources market offers long term resource supply security that Germany needs, especially for strategic metals. Germany, in return, provides market‐leading equipment and specialty services that can help to meet the challenges of the Canadian mining industry today. On the initiative and with funding of the Federal Ministry for Economic Affairs and Energy, the Canadian German Chamber of Industry and Commerce Inc. in 2012 established a Competence Centre for Mining and Mineral Resources to foster business relationships between Canada and Germany in the mining sector.